TINJAUAN SIYASAH SYAR’IYYAH TERHADAP PENGELOLAAN PENDAPATAN ASLI DAERAH DALAM PEMBANGUNAN DAERAH KOTA PALOPO - Saleh, Budiman; Khalik, Subehan; Zakirah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
The main problem of this research is how is the responsibility of the local government towards Regional Original Revenue in the development of Palopo City. This type of research is field research with a normative syar'i approach and empirical juridical which emphasizes adhering to the rationale in accordance with the texts, both Al-Qur'an and hadith, and juridical normative which emphasizes the legislation, while the data sources are primary data obtained directly from the field through interviews and secondary data obtained from library studies, journals on the internet and others. The data collection methods are observation, interview, and documentation methods. Furthermore, data management techniques are carried out by means of data classification, data reduction, data editing and data marking results. The results of the study say that: (1) The local government in managing PAD in Palopo City has tried to implement equitable development by increasing the extensification of regional income, which can be done by managing new sources of revenue and screening new taxpayers/retribution obligors. (2) Regional Original Management in Palopo City which aims to equalize development in Palopo City has been running in accordance with the siyasah syar'iyyah principle although in its realization it is still not fully implemented there are various factors that become obstacles such as lack of public attention about the importance of paying taxes .